2022
DOI: 10.3389/fnbeh.2022.802711
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exercise and Virtual Reality Executive Function Training on Cognition Among Heavy Drinking Veterans With Traumatic Brain Injury: A Pilot Feasibility Study

Abstract: Executive function (EF) underlies self-control deficits in alcohol use disorder (AUD) and traumatic brain injury (TBI). Cognitive training is a promising adjunctive treatment targeting TBI- and AUD- related cognitive dysfunction. However, major limitations related to compliance and generalizability in the field of cognitive training exist. Physical activity is associated with enhanced cognitive performance across several executive functions and may enhance the benefits of cognitive training. Virtual reality pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 102 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…The last decade has witnessed a growing interest in what technology can do to better manage TBI patients. In detail, innovative tools have been implemented in clinical practice to stimulate cognitive recovery following TBI [ 21 , 22 ]. However, a few studies have shown the effectiveness of cognitive training using virtual reality (VR) [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last decade has witnessed a growing interest in what technology can do to better manage TBI patients. In detail, innovative tools have been implemented in clinical practice to stimulate cognitive recovery following TBI [ 21 , 22 ]. However, a few studies have shown the effectiveness of cognitive training using virtual reality (VR) [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, innovative tools have been implemented in clinical practice to stimulate cognitive recovery following TBI [ 21 , 22 ]. However, a few studies have shown the effectiveness of cognitive training using virtual reality (VR) [ 21 , 22 , 23 ]. VR tools offer the possibility to adapt the exercises to the patient’s capabilities and needs and monitor their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Participant fatigue was reduced after intervention in Kolakowsky-Hayner et al (2017) and Tefertiller et al (2022) found improved balance and mobility post-intervention which persisted at the 4-week follow-up. Improved cognitive inhibition was reported by Pennington et al (2022) ; however, they found no change in alcohol use or post-concussion symptoms post-intervention.…”
Section: Resultsmentioning
confidence: 85%
“…Five studies did not specify the severity of traumatic brain injury in participants undergoing aerobic interventions, but referred to trauma-induced brain injury ( Hoffman et al, 2010 ; Esquenazi et al, 2013 ; Kolakowsky-Hayner et al, 2017 ; Pennington et al, 2022 ; Tefertiller et al, 2022 ). Full results are presented in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation